Comments: Prevalence of obstructive airway diseases by spirometric indices in non-smoker subjects with IHD and HTN - Oquaish, Tazeen; Arif, Mohd (Lung India, 2013)
The most likely link between chronic obstructive pulmonary disease (COPD) and extra pulmonary effects is that inflammation in the lung periphery "spills over" into the systemic circulation and effects on other organs that may also be affected by the systemic effects of cigarette smoking.